HUBUNGAN ANTARA POLA ASUH ORANG TUA DAN KEPERCAYAAN DIRI SISWA KELAS V SEKOLAH DASAR NEGERI DI KELURAHAN KAPUK - Natalia Angriany Panjaitan; Imaningtyas; Nina Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This purpose of this study was to empirically determine the relationship betweenparental parenting and self-confidence of fifth grade students of public elementaryschools at Kelurahan Kapuk. This study uses quantitative research methods,which is a research approach that uses data in the form of numbers and statisticalanalysis to understand phenomena. The sample in this study were fifth gradestudents of SDN Kapuk 03 Pagi and fifth grade students of SDN Kapuk 12 Petangas many as 92 respondents. The instrument used was a questionnaire with 20statements for variable X and 20 statements for variable Y. The data was thenprocessed and analyzed using the t-test. Based on the t-test calculation, the t-count value is 6.469, while the t-table value is 0.205. So it can be concluded thatthere is a positive relationship between parenting patterns and self-confidence ofgrade V public elementary school students at Kelurahan Kapuk. The strength ofthis relationship is classified in the moderate category. The contribution given bythe parenting variable to self-confidence is 31.7%, while the other 68.3% isinfluenced by other independent variables.